2013
DOI: 10.1002/mas.21365
|View full text |Cite
|
Sign up to set email alerts
|

A decade of plant proteomics and mass spectrometry: Translation of technical advancements to food security and safety issues

Abstract: Agrawal, G.K. et al. (2013). A decade of plant proteomics and mass spectrometry: Translation of technical advancements to food security and safety issues. AbstractTremendous progress in plant proteomics driven by mass spectrometry (MS) techniques has been made since 2000 when few proteomics reports were published and plant proteomics was in its infancy. These achievements include the refinement of existing techniques and the search for new techniques to address food security, safety, and health issues. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 266 publications
(302 reference statements)
1
34
0
1
Order By: Relevance
“…The term phyto-pathoproteomics can be defined as the application of proteomic tools to profile the proteome (total proteins) of pathogen, host and their interactions for understanding different aspects of phytopathology such as pathogenesis, plant disease resistance and molecular interface of plant-pathogen interactions. For a comprehensive history and development of proteomics, the readers can refer elsewhere (Patterson and Aebersold 2003;Thelen 2007;Agrawal et al 2013). …”
Section: A Brief Historical Perspective Of Proteomicsmentioning
confidence: 99%
“…The term phyto-pathoproteomics can be defined as the application of proteomic tools to profile the proteome (total proteins) of pathogen, host and their interactions for understanding different aspects of phytopathology such as pathogenesis, plant disease resistance and molecular interface of plant-pathogen interactions. For a comprehensive history and development of proteomics, the readers can refer elsewhere (Patterson and Aebersold 2003;Thelen 2007;Agrawal et al 2013). …”
Section: A Brief Historical Perspective Of Proteomicsmentioning
confidence: 99%
“…A first such review on the subjecttranslational plant proteomics -was published in the Journal of Proteomics [7], followed by two reviews focusing on the application and translational aspects of plant proteomics in the new fields of nanoproteomics [8] and biofuel crops [9]. Another comprehensive review with particular focus towards plant proteomics application in food security and safety issues was published in Mass Spectrometry Reviews [10].…”
Section: Inppo Achievements and Future Work In Promoting Plant Protementioning
confidence: 99%
“…Thus, in 2011 Hettinga et al [2] reported as many as 192 proteins and Le et al [3] listed as many as 293 unique species, by resorting to various pre-fractionation techniques. An interesting study has also been published by A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 7 (per 100 mL) of the Roche cocktail of five protease inhibitors. Prior to CPLL treatment, one liter of milk was first delipidated by centrifugation and then casein depleted by precipitation at pH 4.6.…”
Section: Introductionmentioning
confidence: 97%